Improved User Interface Design on Mobile Apps “X” Using the Goal Directed Design Method - Gready Michael Martua; Mira Kania Sabariah; Danang Junaedi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Mobile Apps “X” is one of the supporting applications for the Telkom University community that has been downloaded more than 10,000 times and received a rating of 3.9 on the Google Play Store. There are several user reviews that expect an improvement in the Mobile Apps “X” user interface. The problem found is the complexity of seeing the class schedule because they have to go through several menus first. The aim of the research is to improve the application to be even better so as to eliminate the complexity when used. This is a matter of ease of use. After evaluating the application, the SUS score is 61, the Completion Rate for the task of viewing class schedules is 50%, the task of viewing attendance information is 43%, and the Overall Relative Efficiency is 54%. The solution in this research is to improve the user interface using the Goal Directed Design method which will focus on meeting the goals of the user. The results of the improvements are an increase in the SUS score to 82, the Completion Rate for the task of viewing class schedules to 100%, the task of viewing attendance information to 100%, and the Overall Relative Efficiency to 100%. When interviewed at the end of the evaluation, users said that this design had met their goals. Thus, this improvement has become a solution to application problems.